EXISTENIALISM IS A PHILOSOPHICAL DOCTRINE OF HUMAN EXISTENCE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Existentialism (philosophy of existence) is one of the significant philosophical trends of the XX century, the object of study of which is a person responsible for his fate. Prominent representatives of this philosophical trend are Jean-Paul Sartre, Albert Camus, Martin Heidegger, Karl Jaspers and others. The author of the term “Existentialism”, Soren Kierkegaard, believed that the problem of human destiny is central to philosophy. The article provides an ontological analysis of the conditations for the formation of existential philosophy, its forms and the problems of human freedom.
Keywords: man, society, existence, existentalism, life, destiny,absurd,volition, freedom, rebel.